Effect of Hirsutella sinensis Fungus on the Hypothalamic-Pituitary-Adrenal Axis in Lewis Rats with Kidney-Yang Deficiency Syndrome. (20th May 2020) - Zhang, Lizong; Lang, Jiali; Jin, Lu; Jin, Lushuai; Cao, Beibei; Shao, Xia; Fang, Mingsun; Cai, Yueqin; Liu, Xia; Fu, Huiying; Shou, Qiyang
Abstract : Kidney-yang deficiency syndrome (KYDS) is a classic syndrome in traditional Chinese medicine, which is mainly caused by damage to the hypothalamic-pituitary-adrenal (HPA) axis. Hirsutella sinensis fungus (HSF), an artificial substitute of Cordyceps sinensis, has been widely used in TCM. However, the effects and the possible mechanism of HSF on the HPA axis and corresponding KYDS have not yet been investigated. In this study, Lewis rats were used as a spontaneous KYDS model. HSF was intragastrically administered to the Lewis rats at two doses: low dose (1 g/kg) and high dose (2 g/kg). Body weight, temperature, and behavioral tests including grip strength, open field, and Morris water maze (MWM) tests were used to evaluate the KYDS symptoms. Enzyme-linked immunosorbent assay was used to detect the level of circulating adrenocortisol (ACTH), corticosterone (CORT), corticotropin releasing hormone (CRH), cyclic adenosine monophosphate (cAMP), and cyclic guanosine monophosphate (cGMP). In addition, mRNA expression of tumor necrosis factor alpha (TNF- α ), interferon gamma (IFN- γ ), interleukin 10 (IL-10), CRH, glucocorticoid receptor (GR), and mineralocorticoid receptor (MR) was detected by quantitative real-time polymerase chain reaction (Q-PCR). The Lewis rats were indicated to have KYDS symptoms and HSF treatment ameliorated these symptoms via enhancement of the HPA axis function, which was evidenced by the increased levels of CRH, ACTH, and CORT in serum and 17-OHCS in urine. HSF also significantly improved the expression of TNF- α, IFN- γ, and IL-2, secreted by Th1 cells, which might accelerate the activation of the immune system related to the HPA axis function. Thus, we conclude that HSF can alleviate KYDS symptoms in Lewis rats by regulating the HPA axis through accelerated immune system activation.